Temporary use of glucose sensors in type 1 diabetes patients on continuous subcutaneous insulin infusion - Zivkovic, Marija; Petrovski, Goran; Shubeska Stratrova, Slavica (My University, 2020)
Background and Aims: The aimof this study was to evaluate the impact of temporary use of real-time continuous glucose monitoring (RT-CGM) on glycemic ontrol in patients with type 1 diabetes (T1D) on continuous subcutaneous insulin infusion (CSII). Methods: The retrospective analysis was performed in patients with T1D on CSII, Minimed 754 (Medtronic, Northridge, CA) with HbA1c>7.5%. Minilink transmitter with Enlite Sensors (Medtronic, Northridge, CA) was used as RT-CGM, which was connected to the CSII for seven days at the beginning, 3 months and 6 months. One-hour training session on how to use the sensor was obtained in all patients prior CGM start. Data was downloaded using CareLink Therapy Management. Software (Medtronic, Northridge, CA) and specific changes in basal and bolus insulin, re-education on carb-counting, physical activity and hypoglycemia/ hyperglycemia were given to the patients. HbA1c was obtained before, 3 months and six months after the study. Results: 76 patients (age 18.4±4.9 years) with diabetes duration of 7.8±2.3 years ans CSII use of 2.7±0.9 years were enrolled in the study. The mean HbA1c decreased from 7.9±0.7% at baseline to 7.1±0.5% at the end of the study (p=0.03). Re-education was performed on the following topics: carb counting 43%, hypoglycemia/hyperglycemia treatment 29% and physical exercise 21% of the patients. Conclusions: Temporary use of CGM can improve glycemic control in T1D patients on CSII. Further investigation on larger groups should be performed to confirm our finding.